The effectiveness of pvd installation in bauxite residue soil by using plaxis 2d for settlements analysis - Othman, Noor Aini (2018)
The construction of an embankment on soft soil always leads to settlements. Bauxite residue soil has similar behaviour to clayey soils which consider as soft soil. This study focused on the effectiveness of Prefabricated Vertical Drain (PVD) installation in bauxite residue soil for settlements analysis. Data were collected from in-situ investigation and laboratory testing. PVD at different spacing and length have been used to analyse soil settlement and supported by Asaoka method. The results proved that PVD was able to accelerate the consolidation process and suitable to be used as soft ground improvement technique. Different PVD spacing and length affect the soil settlements analysis in term of settlement depth, settlement rate and excess pore water pressure. 0.5 m PVD spacing has fastest achieved required settlements at day 10 and at 13 m PVD length has highest rate dissipation with excess pore pressure 0.0030 kN/m2. Further studies can be done to propose the practical PVD installation in terms of PVD spacing and length.